E-prescribing and access to prescription medicines during lockdown: experience of patients in Aotearoa/New Zealand - Fiona Imlach; Eileen McKinlay; Jonathan Kennedy; Caroline Morris; Megan Pledger; Jacqueline Cumming; Karen McBride-Henry (BMC Family Practice, 2021)
Abstract Background Health services internationally have been compelled to change their methods of service delivery in response to the global COVID-19 pandemic, to mitigate the spread of infection amongst health professionals and patients. In Aotearoa/New Zealand, widespread electronic delivery of prescriptions (e-prescribing) was enabled. The aim of the research was to explore patients’ experiences of how lockdown, changes to prescribing and the interface between general practices and community pharmacy affected access to prescription medications. Method The research employed a mixed-method approach. This included an online survey (n = 1,010) and in-depth interviews with a subset of survey respondents (n = 38) during the first COVID-19 lockdown (March–May 2020). Respondents were recruited through a snowballing approach, starting with social media and email list contacts of the research team. In keeping with the approach, descriptive statistics of survey data and thematic analysis of qualitative interview and open-ended questions in survey data were combined. Results For most respondents who received a prescription during lockdown, this was sent directly to the pharmacy. Most people picked up their medication from the pharmacy; home delivery of medication was rare (4%). Survey and interview respondents wanted e-prescribing to continue post-lockdown and described where things worked well and where they encountered delays in the process of acquiring prescription medication. Conclusions E-prescribing has the potential to improve access to prescription medication and is convenient for patients. The increase in e-prescribing during lockdown highlighted how the system could be improved, through better feedback about errors, more consistency across practices and pharmacies, more proactive communication with patients, and equitable prescribing costs.